Macrosyntax and pragmalinguistics - Fuentes Rodríguez, Catalina (Círculo de Lingüística Aplicada a la Comunicación, 2017)
Linguistic constructions higher than sentence are analyzed with models based on the structure of the clause, or from the speech acts theory, forgetting, and sometimes questioning, the existence of a syntax. In this paper we want to present a methodological alternative. We defend the existence of a syntax of units higher than the sentence (macrosyntax), which entails the study of the statement, its structure, relationships with others utterances and the higher units in which it is included, both in spoken and written language. The methodological approach, from our point of view, must integrate the componential model with a pragmatic approach, since we are talking about speech acts in a context and in an interactive environment. The presence of all these elements is codified in specific units of discourse as well as in structures and functions. We will apply the pragmalinguistic model already explained in Fuentes Rodríguez (2000) and show how this model can explain many of the problems in the macrosyntax and provides sufficient tools and criteria for the advancement of research.
Keywords: macrosyntax; pragmalinguistics; discursive categories; sentence structure; syntactic relationships.